ANALISIS TINGKAT PEMAHAMAN DALAM MENYUSUN LAPORAN KEUANGAN BERDASARKAN SAK ETAP PADA UMKM DI KECAMATAN SEKUPANG BATAM - Hidayat, Muhammad (MEASUREMENT : Jurnal Program Studi Akuntansi, 2015)
This study aims to determine the level of understanding of the Micro, Small and Medium Enterprises (SMEs) in the preparation of financial statements accordance to SAK ETAP in Sekupang districts Batam City. This research uses descriptive quantitative research methods and data analysis using descriptive statistics percentage. The results showed that the level of understanding of SMEs in the district Sekupang Batam City in applying SAK ETAP is still low which 85% of SMEs do not understand about the application of SAK ETAP. This is because SMEs in District Sekupang still classified as microbussines, and there were perception that accounting is difficult and not important.. The other thing is the lack of information and dissemination of relevant parties in delivering SAK ETAP and SMEs in the District Sekupang Batam City not yet maximal to utilize the information technology that exists today. Keywords: Level of understanding, SAK ETAP, Micro Small and Medium enterprises (SMEs)